1987
DOI: 10.1016/0014-5793(87)80504-5
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme and organic solvents: Horse liver alcohol dehydrogenase in non‐ionic microemulsion: Stability and activity

Abstract: In a microemulsion made with Triton X-100, the stability of the enzymatic activity was higher than in ionic microemulsions. The stability increased with water content. The kinetic constants (Michaelis constant of NAD ÷ and maximum velocity) were close to those found in the previously studied microemulsions. The Michaelis constant of NAD ÷ expressed with respect to the buffer volume was higher than in water. The pH dependence of the kinetic constants in this microemulsion was determined. The activity determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 12 publications
(11 reference statements)
1
8
0
Order By: Relevance
“…The T/max was higher at wo = 10, where the ratio V,,,/K,,, amounted to 21% of that in buffer. These results are similar to the data obtained for other enzymes [3]. The effect of water volume fraction (8) in the catecholase activity at (JO constant (WO = 10) is shown in fig.4a.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The T/max was higher at wo = 10, where the ratio V,,,/K,,, amounted to 21% of that in buffer. These results are similar to the data obtained for other enzymes [3]. The effect of water volume fraction (8) in the catecholase activity at (JO constant (WO = 10) is shown in fig.4a.…”
Section: Resultssupporting
confidence: 89%
“…Although a number of enzymes have been investigated in such media, most work has been carried out on hydrolases (a-chymotrypsin and lipases) and dehydrogenases but not on oxidases [l]. The surfactants mostly employed are AOT, CTAB, SDS and Triton X-100 [3] but only few enzymes have been entrapped in Brij 96 [4]. We describe here for the first time some kinetic parameters of a mem- The standard reaction media contained 0.5 mM 4-methyl catechol, 0.166 M Brij 96, ~0 = 10, B = 0.6%, 15 pg/ml of PPO in 50 mM acetate buffer, pH 5.0, at 25"C, unless stated otherwise.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of SDS microemulsion, the velocity increased as the water content increased but in CTAB microemulsion, the velocity did not show a clear dependence on the water content. The same group studied the behavior of HLADH in a cyclohexane/Triton X-100/1-butanol/water system where 1-butanol worked as both co-surfactant and a substrate [108]. They concluded that the enzyme in the above microemulsion has a higher stability over time in comparison to other microemulsions with anionic surfactants.…”
Section: Dehydrogenasesmentioning
confidence: 99%
“…While lipases, for example, show good stabilities in several organic reaction media (Stamatis et al, 1999), alcohol dehydrogenases are less stable, having half-life times in microemulsions of only hours (Chen et al, 1995;Lee and Biellmann, 1987;Orlich and Schomäcker, 1999a) or even minutes (Samama et al, 1987). The stability depends on the microemulsion parameters and additionally on the reaction components and salts, mainly the water and the surfactant concentration.…”
Section: Introduction Generalmentioning
confidence: 99%